Deoxygenated porous carbon with highly stable electrochemical reaction interface for practical high-performance lithium-ion capacitors. (21st October 2021) - An, Yabin; Li, Chen; Sun, Xianzhong; Wang, Kai; Su, Fangyuan; Liu, Fangyan; Zhang, Xiong; Ma, Yanwei
Abstract: Metal-ion capacitors, especially lithium-ion capacitors (LICs), are promising energy storage devices with much higher energy density than conventional electrochemical double-layer capacitors (EDLC). While compared with the EDLCs, the stable voltage window of the cathode in LICs is much narrower than that in EDLCs because of the different energy storage mechanisms, which restricts the energy density of LICs. In this work, the porous carbon (D-HAC) with an ultra-low oxygen element content of 0.973 wt.% is synthesized by heating the starch-based porous carbon (HAC) in the hydrogen-argon mixing atmosphere. The specific capacitance of D-HAC reaches up to 106.7 F g −1 at 50 mA g −1 . Owing to high specific capacitance of D-HAC, LIC constructed with D-HAC cathode and soft carbon anode can provide a high energy density of 123.5 Wh kg −1 . More importantly, the D-HAC//SC LIC shows excellent capacity retention of 96.77% after 10 000 cycles at a high rate of 50 C due to the stable electrochemical interface of D-HAC. This work provides a simple and efficient method to remove the unstable oxygen element of the porous carbon materials and shows a promising approach to develop advanced metal-ion capacitors with high energy density and long cycle life.